The evolution of the academic profession in research universities in Chile - Veliz-Calderon, Daniela; Theurillat, Daniel; Paredes, Victoria; Pickenpack, Astrid (Education Policy Analysis Archives, 2018)
Faculty members are fundamental for the development and success of higher education organizations, and building strong academic cadres is a major challenge, especially for research universities. While there are no fully-fledged research universities in Chile (Bernasconi, 2007), a few strive to get closer to that ideal by way of the professionalization their faculty. This study follows this process guided by the question “How do academic rules and guidelines in six research-oriented universities in Chile reflect the professionalization of the academic profession from 1967 to 2016?” Findings show that universities have converged in the structure they provide for their tenured and tenure-track faculty. The requirements to enter the “tenure track” career have become stricter over time, while adjunct faculty experience little regulation of their duties, governance rights, and benefits, even though they still constitute the highest proportion of faculty members overall. Lastly, it seems that these universities have changed their academic regulations over time as a response to internal processes rather than external pressures.